Dietary zinc status in offspring of pregnant rats fed on a zinc-deficient diet is associated with Serum Albumin, Ast, and Alt levels - Gümüş, Meltem; Baltacı, Saltuk Buğra (Pera Publishing Services, 2023)
Objective: This study was carried out to investigate whether dietary zinc status is associated with serum albumin, AST and ALT levels in male offspring of mother rats fed a zinc deficient diet. Methods: The study was carried out on male offspring (Groups 1, 2, 3) born to rats fed a zinc deficient diet and on male offspring (Group 4) born to mothers fed a standard diet. Group 1: Zinc deficient, Group 2; standard rat chow, Group 3: Zinc supplemented diet. Animals of group 4 were used as control group. After the completion of the experimental stages of the study, albumin, AST, ALT, free and total bilirubin levels in serum samples taken from animals were determined by spectrophotometric method. Results: Dietary zinc deficiency (group 1) significantly decreased serum albumin values (p<0.004). Animals in both the zinc deficient (Group 1) group and the Group 2 animals born to mothers fed a zinc deficient diet and fed standard rat chow had the highest AST and ALT levels (p<0.001). Conclusion:The present study is the first to show that dietary zinc status can directly affect liver function in rats born to zinc deficient mothers by causing changes in serum albumin, AST and ALT levels.
Keywords: Maternal Zinc Deficiency; Zinc; Albumin; AST; ALT; Male Offspring Rat